Analysis of Agricultural Water Use Efficiency in Shandong Province Based on DEA and Malmquist Model. Issue 1 (October 2020) - Yuyu, Liu; Jingjing, Geng; Linlin, Zhang; Xin, Jiang; Yongfei, Fu; Lin, Lin
Abstract: Water resource shortage has become a restricting factor for social and economic development. Improving water use efficiency of agriculture is an important way to alleviate water resource pressure and ensure food security. Based on DEA and Malmquist models, this paper calculated and analyzed the technical efficiency, scale efficiency and pure technical efficiency of agriculture using panel data from 17 cities in Shandong province from 2007 to 2017. Then, panel data of grains, beans, tubers, oils, cotton and vegetables were selected for the analysis of water use efficiency. The results showed that: (1) the water use efficiency of agriculture in Shandong Province increased year by year; (2) there are significant differences in water use efficiency of agriculture among cities; Qingdao, Jinan and Yantai are higher, while Dezhou and Heze are lower. (3) oil and cotton are the crops with the highest water use efficiency in agriculture in Shandong province. Under the premise of ensuring the required crop production, more oil and cotton can be considered to be planted.